The fading distinctiveness in the roles of author, publisher and bookseller in book development: implications for the emerging information society and Nigerian book industry (2011)
The paper defines who an author, a publisher, and a bookseller is and expatiated on the indispensable roles of these key actors in book development in Nigeria. The present fading distinctiveness of these three roles and its implications for the emerging Information Society and the Nigerian Book Industry is the main thrust of the paper. The paper advised on how the Book industry in Nigeria can be further promoted so as to enhance scholarship in the country.